Prediction of User Behaviour on the Basis of Key Determinants of Sustainability for Wall Paints Used in Construction with the Help of the Analytic Hierarchy Process - Rochikashvili, Mariia; Bongaerts, Jan C. (Journal of Environmental Accounting and Management, 2026)
The choice of a product according to criteria, such as price, applicability, quality, environmental safety, health etc. requires knowledge on its properties, e.g. as available in product descriptions, instructions for use, and for some categories of products, such as wall paints, in Material Safety Data Sheets (MSDS). Professional experts have the abilities to analyse and assess this information, but non-expert users may lack such capabilities. Even so, they reveal their preferences through purchasing decisions. Hence, it is important to develop a research methodology to understand their decision-making. In this paper, such a methodology is developed, based on the Analytic Hierarchy Process and the use of the SuperDecisions software for the case of indoor wall paints. The outcome is a model which can be used for the purpose of analysing and understanding nonexpert users’ behaviour when selecting such an indoor wall paint.